TermPicks : a century of Greenland glacier terminus data for use in machine learning applications - Goliber, Sophie; Black, Taryn; Catania, Ginny; Lea, James; Olsen, Helene; Cheng, Daniel; Bevan, Suzanne; Bjork, Anders; Bunce, Charlie; Brough, Stephen; Carr, Rachel; Cowton, Tom; et al. (2022)
Authors acknowledge support from a NASA Earth and Space Sciences fellowship to Sophie Goliber (18-EARTH18F-323) and terminus tracers everywhere. Niels J. Korsgaard was supported by the Programme for Monitoring of the Greenland Ice Sheet (PROMICE). Michael Wood was supported by an appointment to the NASA Postdoctoral Program at the Jet Propulsion Laboratory, California Institute of Technology, administered by the Universities Space Research Association under contract with NASA. James M. Lea is supported by a UKRI Future Leaders Fellowship (grant no. MR/S017232/1). Dominik Fahrner acknowledges support for this study through the EPSRC and ESRC Centre for Doctoral Training on Quantification and Management of Risk and Uncertainty in Complex Systems Environments (grant no. EP/L015927/1). Tavi Murray is funded by the Leverhulme Trust Research Leadership scheme F/00391/J and the UK NERC NE/G010366/1. Marine-terminating outlet glacier terminus traces, mapped from satellite and aerial imagery, have been used extensively in understanding how outlet glaciers adjust to climate change variability over a range of timescales. Numerous studies have digitized termini manually, but this process is labor intensive, and no consistent approach exists. A lack of coordination leads to duplication of efforts, particularly for Greenland, which is a major scientific research focus. At the same time, machine learning techniques are rapidly making progress in their ability to automate accurate extraction of glacier termini, with promising developments across a number of optical and synthetic aperture radar (SAR) satellite sensors. These techniques rely on high-quality, manually digitized terminus traces to be used as training data for robust automatic traces. Here we present a database of manually digitized terminus traces for machine learning and scientific applications. These data have been collected, cleaned, assigned with appropriate metadata including image scenes, and compiled so they can be easily accessed by scientists. The ...